2017
DOI: 10.15406/atroa.2017.03.00066
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineered organoids for neural network modelling

Abstract: The increased prevalence of neurological diseases across the world has stimulated a great deal of research into the physiological and pathological brain, both at clinical and pre-clinical level. This has led to the development of many sophisticated tissue engineered neural models, presenting greater cellular complexity to better mimic the central nervous system niche environment. These have been developed with the ambition to improve pre-clinical assessment of pharma and cellular therapies, as well as better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 135 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Other reviews also cover the necessary considerations for in vitro modelling design, along with recent advances from 2D culture systems to 3D organoids and bio-artificial organs. 208 , 211 …”
Section: Microfluidic Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Other reviews also cover the necessary considerations for in vitro modelling design, along with recent advances from 2D culture systems to 3D organoids and bio-artificial organs. 208 , 211 …”
Section: Microfluidic Technologymentioning
confidence: 99%
“…34,35 The combination of lab-on-a-chip technology with specific organ characteristics, such as interstitial fluid flow (osmotic pumps) in the case of the brain, makes it possible to create organ (brain)-on-a-chip platforms. 208 Organ-ona-chip devices can replicate fundamental aspects of animal physiology essential for the understanding of drug effects, improving preclinical safety and efficacy testing. 11 Park et al 209 demonstrated that the neural network formation in neurospheroids was significantly reinforced by fluidic flow on a microfluidic device.…”
Section: Microfluidic Technologymentioning
confidence: 99%
“…In vitro 3D models especially have enabled the development of more relevant models recapitulating for brain complex functional connectivity patterns (Jorfi et al, 2018). These models, particularly brain organoids, can recreate several intricate features of the CNS and PNS via co-culturing different subtypes of neuronal cells that self-organize into microstructures (Roach et al, 2017;Osaki et al, 2018a;Ali et al, 2019;Nikolakopoulou et al, 2020). Brain organoids can be used to recapitulate the heterogeneity of neural cells, however scaling up the intrinsic 3D organizational complexity of the human brain is limited to only some specific brain regions (Hasan and Berdichevsky, 2016;Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%